Power, speed, endurance : a skill-based approach to endurance training - MacKenzie, Brian, ....-; Cordoza, Glen, ....- ([s.l.] : Victory Belt Publishing, 2012)
In this book, you will learn how to: develop proper running technique using the Pose Method properly fit yourself on a bike improve cycling mechanics on a road, time-trial, and mountain bike swim effortlessly and improve freestyle-stroke mechanics through skill-based drills and exercises accelerate work capacity and minimize fatigue by building muscle, speed, and power incorporate a CrossFit Endurance strength-and-conditioning program into your training routine maximize nutrition, hydration, and electrolyte balance to improve performance and body composition prevent, repair, and treat nagging injuries associated with endurance sports and improve range of motion using Starrett's Movement and Mobility Method
Power, Speed, ENDURANCE is a highly effective training system that has catapulted thousands of endurance athletes to the next level. Developed by CrossFit Endurance founder Brian MacKenzie and featuring instruction from some of the world's top endurance and CrossFit coaches, Power, Speed, ENDURANCE unveils techniques, drills, and training strategies that will optimize your performance and overall work capacity while decreasing your susceptibility to injury. Through thousands of step-by-step color photographs and detailed narrative, Power, Speed, ENDURANCE breaks down proper running, cycling, and swimming mechanics like never before. MacKenzie's unique system of building strength, speed, and power is aimed at reaping continual results, without injury. In fact, he devotes an entire chapter to the "broken down" athlete, equipping you with the knowledge to prevent, repair, and treat injuries brought on by poor mechanics and tight overworked muscles. In addition, MacKenzie outlines a straightforward approach to nutrition, hydration, and electrolyte balance that will increase your energy, boost your performance, and accelerate your recovery. Whether you're a self-trained athlete looking to compete in your first endurance event, a seasoned competitor looking to reach your highest potential, or a CrossFit athlete looking to increase stamina, Power, Speed, ENDURANCE will help you reach your goal.
Keywords: Krachttraining ; uithouding